MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN MATEMATIKA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS VII MTSS DARUSSALAM AMPING PARAK - Sefrinal, Sefrinal; Syafti, Okviani; Arif, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
This research is motivated by the monotonous teacher teaching method, which requires students to remember the material without asking to understand the concept of learning mathematics. So that mathematics learning has not achieved the expected results. To solve this problem, the Discovery Learning model (guided discovery) is a solution that will be tried. The goal is that there is a change in student learning attitudes and teacher teaching so that they will get good learning outcomes and achieve KKM. This research model uses a quantitative approach with experimental methods, with a random research design on the subject. The population in this study were students of class VII MTsS Darussalam Amping Parak for the 2020/2021 academic year which consisted of two classes. The sampling technique was carried out randomly, class VIIB as the experimental class and VIIA as the control class. The instrument used in this study was a reliable essay final test. The data analysis technique used is the one-party t test. Hypothesis testing using the one-party t-test, obtained t = 3.21 and t table = 1.67. Because tcount> ttable, this research hypothesis is accepted. So, it can be concluded that the mathematics learning outcomes of students using the Discovery Learning Model are better than the mathematics learning outcomes of students taught using conventional learning in class VII students of MTsS Darussalam Amping Parak for the 2020/2021 academic year